In Bitcoin We Trust. - Thompson, Clive (Smithsonian, 2018)
The article reports on the history of money in the U.S. It mentions the use of bank notes as a form of private currency, the issue of counterfeiting money, and the use of Bitcoin and other cryptocurrencies to get around government control of the creation of money.